2011
DOI: 10.1097/igc.0b013e31823105ed
|View full text |Cite
|
Sign up to set email alerts
|

A Novel CRAd in Combination With Cisplatin Enhanced the Antitumor Efficacy in Ovarian Cancer

Abstract: CDDP - cisplatin, cis-diamminedichloroplatinum, CRAd - conditionally replicating adenovirus, CRAd-survivin - the survivin promoter-based conditionally replicating adenovirus, CRAd-S.RGD - CRAd-survivin-RGD4C, MOI - multiplicity of infection, PBS - phosphate-buffered saline, PI - propidium iodide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…A similar adenoviral agent to ours (CRAd-S-RGD [arginine-lysine-aspartate]) was also investigated in combination with cisplatin for ovarian cancer. Their virus results in synergistically increased efficacy in a xenograft flank tumor model without a concomitant increase in toxicity 43 . The RGD modification on the fiber knob domain of this virus enhances tumor cell infection via integrins instead of the polylysine-facilitated infection in our virus that utilizes proteoglycans.…”
Section: Discussionmentioning
confidence: 99%
“…A similar adenoviral agent to ours (CRAd-S-RGD [arginine-lysine-aspartate]) was also investigated in combination with cisplatin for ovarian cancer. Their virus results in synergistically increased efficacy in a xenograft flank tumor model without a concomitant increase in toxicity 43 . The RGD modification on the fiber knob domain of this virus enhances tumor cell infection via integrins instead of the polylysine-facilitated infection in our virus that utilizes proteoglycans.…”
Section: Discussionmentioning
confidence: 99%
“…Since RGD is an α v -integrin binding motif, the addition of this peptide allows the adenovirus attachment to different integrins, like α v β 3 orα v β 5 , and subsequently the virus infects the cell in a CAR-independent manner [58] . The ability of this modified fiber to mediate adenovirus infection in CAR-negative cells has been exploited in multiple virotherapy studies for a broad range of tumors as for example in glioma [59] , [60] , [61] , osteosarcoma [62] , [63] , ovarian cancer [64] , prostate cancer [65] or bladder cancer [66] .…”
Section: Oncolytic Adenoviruses As Therapeutic Tools: Widening Adenovmentioning
confidence: 99%
“…[118][119][120][121] It has been reported that virotherapy combined with chemotherapy is a potential therapeutic modality for the improvement of transfection efficiency and therapeutic efficacy for ovarian cancer. 122,123 Zhang et al demonstrated a synergistic effect in the combination of a novel surviving promoter-based conditionally replicating adenovirus and cisplatin in the enhancement of the antitumor efficacy in ovarian cancer while Franke et al reported that tobacco mosaic virus delivered cisplatin restored efficacy in platinum-resistant ovarian cancer cells. 122,124 In addition, It is reported that some microtubule-disrupting drugs, such as PTX, can improve gene transfection efficiency at a non-cytotoxic dosage.…”
Section: Codelivery Of Viral Gene and Anticancer Drugmentioning
confidence: 99%